Oncogenic potential of truncated RXRα during colitis-associated colorectal tumorigenesis by promoting IL-6-STAT3 signaling - Xiaohong Ye (Nature Portfolio, 2019)
The truncated form of retinoid X receptor-alpha is found in cancer. Here, the authors show that this mutant receptor promotes colorectal tumorigenesis by activation of NF-κB in myeloid cells, leading to subsequent IL-6-induced STAT3 activation in intestinal epithelial cells, which can be suppressed by ligand K-80003.